The photosynthetic apparatus and its regulation in the aerobic gammaproteobacterium Congregibacter litoralis gen. nov., sp. nov. - Stefan Spring (Public Library of Science (PLoS), 2009)
Background There is accumulating evidence that in some marine environments aerobic bacteriochlorophyll a-producing bacteria represent a significant part of the microbial population. The interaction of photosynthesis and carbon metabolism in these interesting bacteria is still largely unknown and requires further investigation in order to estimate their contribution to the marine carbon cycle. Methodology/principal findings Here, we analyzed the structure, composition and regulation of the photosynthetic apparatus in the obligately aerobic marine gammaproteobacterium KT71(T). Photoheterotrophically grown cells were characterized by a poorly developed lamellar intracytoplasmic membrane system, a type 1 light-harvesting antenna complex and a photosynthetic reaction center associated with a tetraheme cytochrome c. The only photosynthetic pigments produced were bacteriochlorophyll a and spirilloxanthin. Under semiaerobic conditions KT71(T) cells expressing a photosynthetic apparatus showed a light-dependent increase of growth yield in the range of 1.3-2.5 fold. The expression level of the photosynthetic apparatus depended largely on the utilized substrate, the intermediary carbon metabolism and oxygen tension. In addition, pigment synthesis was strongly influenced by light, with blue light exerting the most significant effect, implicating that proteins containing a BLUF domain may be involved in regulation of the photosynthetic apparatus. Several phenotypic traits in KT71(T) could be identified that correlated with the assumed redox state of growing cells and thus could be used to monitor the cellular redox state under various incubation conditions. Conclusions/significance In a hypothetical model that explains the regulation of the photosynthetic apparatus in strain KT71(T) we propose that the expression of photosynthesis genes depends on the cellular redox state and is maximal under conditions that allow a balanced membrane redox state. So far, bacteria capable of an obligately aerobic, photosynthetic metabolism constitute a unique phenotype within the class Gammaproteobacteria, so that it is justified to propose a new genus and species, Congregibacter litoralis gen. nov, sp. nov., represented by the type strain KT71(T) ( = DSM 17192(T) = NBRC 104960(T)).